Chloride Diffusion and Induced Reinforcement Corrosion in Concrete with Fly Ash and Ground-Granulated Blast-Furnace Slag Exposed to Marine Submerged Zone. (23rd December 2020) - Zhao, Rui; Jin, Zuquan; Feng, Guangyan; Li, Jianqiang
Abstract : This paper investigates the influence of mineral admixtures fly ash (FA) and ground-granulated blast-furnace slag (GGBS), the byproducts of industry, on chloride ions migration and corrosion resistance performance. A novel preparation method of wire beam electrode (WEB) was also introduced to explore the excellent corrosion-resistant capacity of concrete with mineral admixtures. By comparing concrete specimens with and without FA and GGBS, the test result of wire beam electrode, rapid chloride migration (RCM), and electrochemical tests highlight the positive impact of fly ash and GGBS against chloride ions migration, respectively. Concrete with fly ash and GGBS supplies an advanced protection effect of ordinary Portland cement; meanwhile, CO2 emission amount can be significantly reduced. Moreover, homemade wire beam electrode was proved to be a novel and reliable test method against corrosion, which has agreement with the test result of an electrochemical device.